THE ROLE OF DEPOSIT INSURANCE IN SUPPORTING ISLAMIC MICROFINANCE INSTITUTIONS: INSIGHTS FROM INDONESIA - Fianto, Bayu Arie; Aryo, Bagus; Shah, Syed Alamdar Ali; Mustofa, Muhammad Ubaidillah Al; Anisha, Ade Intan Ismi Nur; Ruslan, Rafiatul Adlin Hj Mohd (Bank Indonesia, 2025)
This study assesses the necessity of a Deposit Insurance System (DIS) for Islamic Microfinance Institutions (IMFIs). It first identifies key factors influencing knowledge of DIS among stakeholders and then proceeds to evaluate the social impact of IMFIs and examine the urgency for a DIS and respondents' willingness to pay deposit insurance premiums. Conducting survey using purposive sampling, we obtain required data for the analysis from 405 respondents. Applying the logistic regressions, we find reveal that education, work experience, and financial behaviors influence DIS awareness. The findings underscore the urgency of implementing DIS to bolster stakeholder trust and financial system stability, with respondents expressing willingness to contribute premiums. These insights contribute to designing a Shariah-compliant DIS that aligns with the unique operational characteristics of IMFIs, supports sustainable industrialization, and advances SDG-9 goals. The study highlights actionable pathways for policymakers, regulatory bodies, and IMFI managers to foster a resilient and inclusive financial ecosystem. ACKNOWLEDGEMENT Special thanks to the National Committee of Islamic Economic and Finance of the Republic of Indonesia and Universitas Airlangga for the financial assistance. Universitas Airlangga through International Research Collaboration Scheme Top #500, Airlangga Research Fund, Year 2023, Universitas Airlangga, No: 359/UN3.15/PT/2023.